Length scale dependent deformation in natural rubber. Issue 43 (25th July 2015) - Chandrashekar, Gurudutt; Alisafaei, Farid; Han, Chung‐Souk
ABSTRACT Strong length scale dependent deformation has been previously observed in the elastomer polydimethylsiloxane by indentation type experiments at micro‐ to nanometer length scales with a sharp conical tip. To examine if other nonsilicone based elastomers exhibit similar length scale dependent deformation behavior, natural rubber has been chosen in this study. Performing indentation type tests with a nanoindentation system, the universal hardness and the elastic modulus are determined at different probing depths ranging from about 90 to 5 μm to characterize length scale dependent deformation behavior in natural rubber. The testing with a Berkovich tip resulted in an amazing increase in the universal hardness with decreasing probing depth indicating that the deformation mechanisms at the micrometer length scales are significantly different as compared to those at the macroscopic length scales. The observed length scale dependent deformation is associated with an increase in rotation gradients with decreasing probing depth. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42683.